The role of facet join angle in spondylolisthesis - A radiologic study - (:unkn) unknown (SPRINGER WIEN, 1999)
Several factors play a role in the etiology of the degenerative spinal processes. This study examined the role of facet angle in the etiology of degenerative spondylolisthesis and lumbar spinal stenosis. In order to measure the facet angles, computerized tomographic scans of 18 patients with degenerative spondylolisthesis and 11 patients with lumbar spinal stenosis were reviewed and the results were compared with the results of the control group. A significantly more sagittal orientation was found in facet joint angles of the patients with degenerative spondylolisthesis and with lumbar spinal stenosis, when compared with the control group. It is concluded that more sagittal orientation of the facet joint angle may play a role in the pathogenesis and progression of the degenerative spondylolisthesis, and that this fact should be taken into consideration in cases which need extensive decompression for degenerative spondylolisthesis.
Keywords: degenerative spondylolisthesis; facet angle; lumbar spinal stenosis; INTERVERTEBRAL-DISK; DEGENERATIVE SPONDYLOLISTHESIS; ASYMMETRY; ORIENTATION; HERNIATION; MORPHOLOGY